2006
DOI: 10.1007/s10529-006-9127-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of relative mRNA quantification models and the impact of RNA integrity in quantitative real-time RT-PCR

Abstract: Relative quantification in quantitative real-time RT-PCR is increasingly used to quantify gene expression changes. In general, two different relative mRNA quantification models exist: the delta-delta Ct and the efficiency-corrected Ct model. Both models have their advantages and disadvantages in terms of simplification on the one hand and efficiency correction on the other. The particular problem of RNA integrity and its effect on relative quantification in qRT-PCR performance was tested in different bovine ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
403
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 507 publications
(418 citation statements)
references
References 19 publications
12
403
0
3
Order By: Relevance
“…Total RNA quantity and integrity were evaluated using RNA 6000 Nano Chip in a Bioanalyzer 2100 (Agilent Technologies). Total RNA was judged to be acceptable if the ribosomal fragments were present in a 28S/18S ratio over 1.5 and RNA integrity number (RIN) to be over 6 (Fleige et al 2006). RNA samples were stored at -80°C until use for microarray hybridizations and qPCR analysis.…”
Section: Rna Isolationmentioning
confidence: 99%
“…Total RNA quantity and integrity were evaluated using RNA 6000 Nano Chip in a Bioanalyzer 2100 (Agilent Technologies). Total RNA was judged to be acceptable if the ribosomal fragments were present in a 28S/18S ratio over 1.5 and RNA integrity number (RIN) to be over 6 (Fleige et al 2006). RNA samples were stored at -80°C until use for microarray hybridizations and qPCR analysis.…”
Section: Rna Isolationmentioning
confidence: 99%
“…After subtracting the threshold cycle (C T ) value for GUS from the C T values of the target genes, the DC T values were converted with the formula 2 ÀDDCT to show the foldrelative increase in MIC-A, ULBP2 and ULBP3 mRNA expression compared with the levels before treatment, which were given the arbitrary value of 1. 20 …”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…The amount of target relative to reference sample was calculated as 2 ÀDDCt , as described earlier. 6 As shown in Table 1, we found that t(4;11) leukemia cells expressed mRNA for EPOR at high levels, but expressed that for vWF, Tie-2 and KDR at low levels or beyond detection. MV4-11 expressed EPOR and VE-cadherin at higher levels, whereas RS4;11 expressed CD34 and SEM-K2 vWF at higher levels.…”
mentioning
confidence: 53%